PERAN KECERDASAN EMOSIONAL GURU DALAM MENCIPTAKAN LINGKUNGAN PEMBELAJARAN YANG HARMONIS PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Ai Silvi Nurhasanah; Shalahudin Ismail; Cakra Sastra Sukma Sejati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Emotional intelligence is one of the important competencies that teachers must have in creating a harmonious environment in dealing with classroom dynamics, especially in Islamic Religious Education (PAI) subjects that are full of moral and spiritual values. This study aims to deeply analyze the role of teachers' emotional intelligence in creating a conducive, peaceful, and supportive learning atmosphere for students' affective development in PAI subjects. The research method used was descriptive qualitative with a case study approach to PAI teachers at the elementary and junior high school levels. Data collection techniques were conducted through observation, in-depth interviews, and documentation. The results showed that teachers' emotional intelligence significantly contributed to creating a harmonious learning atmosphere and supporting students' affective development in PAI learning. Through empathy, effective interpersonal communication, and reflective teaching strategies, teachers are able to build positive relationships and increase active student participation. Therefore, emotional intelligence training for PAI teachers needs to be a concern in the development of teacher professionalism.